Gas-dynamic calculation of technological operating parameters of multilayer gas storage facilities (on the example of Proletarske) - Тимків, Дмитро Федорович; Заєць, Віктор Олександрович; Костів, Ярослава Василівна (Technology audit and production reserves, 2016)
This article analyzes the work of multilayer underground gas storage facility. Practical material was compiled in the basis of this analysis. These data were the basis of the calculation methodology of technological operation parameters for multilayer storage facilities during the injection and extraction of gas. To calculate the technological operation parameters and their dynamics during injection of gas the following data are given. The maximum layer pressure was determined taking into account the capacity of the existing gas compressor units and capabilities to ensure the necessary operating pressure in the mouths of wells. Minimum layer pressure for horizons was adopted for the results of development with regard to provision of anhydrous operation of wells and free-current gas supply to the pipeline-connection at the end of the extraction season. Maximum pressure drawdown was taken as a result of development of deposits and filtration coefficient of resistance – as a result of gas-dynamic studies of wells.